Preparation method of BOPP (biaxially-oriented polypropylene) composite shrink film

By uniformly distributing composite antibacterial particles in the outer layer and base layer of the BOPP composite shrink film, the problem of different heat resistance abilities of different layers is solved, the antibacterial coverage and mechanical properties are improved, and the service life is extended.

CN119502288APending Publication Date: 2025-02-25SHENZHEN XIANZI BIOTECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411655768.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the heat sealing and heat shrinking process of the existing BOPP composite shrink film, the heat resistance of different layers varies, resulting in increased production difficulty and shortened service life.

Method used

By uniformly distributing composite antibacterial particles, including a mixture of nanotitanium dioxide and heat-resistant metal ion particles, in the outer layer and base layer of the BOPP composite shrink film, the particle size and distribution are adjusted to ensure uniform synchronous heat resistance of different layers.

Benefits of technology

The uniform synchronous heat resistance of different layers is achieved, the antibacterial coverage and mechanical properties of the film are improved, the service life is extended, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005142079030000051
    Figure BDA0005142079030000051
Patent Text Reader

Abstract

The invention discloses a preparation method of a BOPP composite shrink film, and relates to the technical field of packaging materials, the BOPP composite shrink film comprises an outer layer, a base layer and a heat sealing layer; the outer layer comprises composite antibacterial particles, a liquid coupling agent, an antioxidant, a dispersing agent, a heat stabilizer, metallocene co-polypropylene, smooth master batch and POE; the base layer comprises polypropylene, a stiffening master batch and an antistatic master batch; the stiffening master batch comprises a mixture of hydrogenated petroleum resin and homo-polypropylene; composite antibacterial particles; the heat-sealing anti-sticking layer is prepared from polypropylene and titanium dioxide anti-sticking master batch; the toughness of the film can be improved, the composite antibacterial particles are uniformly distributed in the two layers, a more uniform antibacterial layer is formed, and the situation that the antibacterial effect is too strong or too weak locally is avoided, so that the overall antibacterial efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, and in particular to a method for preparing a BOPP composite shrink film. Background Art

[0002] BOPP film, full name of biaxially oriented polypropylene film, is a plastic film made by co-extruding polypropylene particles into sheets and then stretching them in both the longitudinal and transverse directions. Although its oxygen barrier performance is average, its moisture barrier performance is good, and its fragrance retention can basically meet the use requirements. Due to its thermoplasticity, it is very suitable for packaging as a shrink film. It is a commonly used thermoplastic polyolefin coil. In the existing technology, multi-layer film composite is often used;

[0003] For example, the Chinese patent, application number CN202310427556.8, a BOPP antibacterial touch shrinkage cigarette film and its preparation method and application, which includes a functional layer, a base layer, and a heat-sealing anti-sticking layer, the base layer is sandwiched between the functional layer and the heat-sealing anti-sticking layer; the functional layer includes the following components in parts by weight: 1-2 parts of composite antibacterial agent, 0.5-1 parts of liquid coupling agent, 0.5-1 parts of antioxidant, 0.1-0.3 parts of dispersant, 0.1-0.3 parts of heat stabilizer, 70-80 parts of metallocene copolymer polypropylene, 5-8 parts of slippery masterbatch, and 10-15 parts of POE. The composite antibacterial agent includes a mixture of nano-titanium dioxide and heat-resistant metal ion antibacterial agent, which has good touch and strong antibacterial properties, and meets the requirements of cigarette film indicators.

[0004] However, only adding a small amount of composite antibacterial agent with antibacterial effect to the functional layer makes it antibacterial and heat-resistant. A small amount of addition is unlikely to affect the properties of the functional layer, while an increase in the amount of addition will lead to a difference in the heat resistance between the functional layer and other layers. The need for process adjustment during heat sealing and heat shrinkage increases the difficulty of preparation, and the agglomeration of particles or the uneven distribution caused by gravity and fluidity, as well as the difference in heat resistance during subsequent use, lead to a reduction in service life. Summary of the invention

[0005] The embodiment of the present application provides a method for preparing a BOPP composite shrink film, thereby solving the problem of different heat resistances of different layers in the prior art and achieving uniform and synchronous heat resistance of different layers.

[0006] The embodiment of the present application provides a method for preparing a BOPP composite shrink film, wherein the BOPP composite shrink film comprises: an outer layer, a base layer, and a heat-sealing layer; the weight proportions of the functional layer, the base layer, and the heat-sealing anti-sticking layer are 3%-8%, 91%-98%, and 1%-5%, respectively; wherein the outer layer comprises: 1-2 parts of composite antibacterial particles, 0.5-1 parts of liquid coupling agent, 0.5-1 parts of antioxidant, 0.1-0.3 parts of dispersant, 0.1-0.3 parts of heat stabilizer, 70-80 parts of metallocene copolymer polypropylene, 5-8 parts of slip masterbatch, and 10-15 parts of POE;

[0007] The base layer includes: polypropylene: 77-89 parts, rigidity masterbatch: 10-20 parts, antistatic masterbatch: 1-3 parts; the rigidity masterbatch includes a mixture of hydrogenated petroleum resin and homopolymer polypropylene; composite antibacterial particles 2-5 parts;

[0008] Heat-seal anti-sticking layer: polypropylene: 95-99 parts, titanium dioxide anti-sticking masterbatch: 1-5 parts.

[0009] Furthermore, the composite antibacterial particles include a mixture of nano titanium dioxide and heat-resistant metal ion particles, with a heat-resistant temperature of 500-600° C. and a D50 particle size of 0.1-10 μm.

[0010] Furthermore, the heat-resistant metal ion particles are submicron glass beads loaded with antibacterial ions, and the antibacterial ions include zinc ions, silver ions, and copper ions.

[0011] A further method for preparing the composite antibacterial particles is to mix heat-resistant metal ion particles composed of 60 parts by weight of submicron glass beads, 15 parts by weight of silver ion salt, 13 parts by weight of zinc ion salt and 10 parts by weight of copper ion salt with nano titanium dioxide in a weight ratio of 1:1.

[0012] Furthermore, the particle size D50 of the composite antibacterial particles in the outer film is 1-3 μm.

[0013] Furthermore, the preparation method of the BOPP composite shrink film includes: feeding the selected raw materials into a melt extruder according to the mass proportion, processing the raw materials into a melt in the melt extruder, passing the melt through a metering extruder, a filter, and a die head, and co-extruding a thick sheet at 200-250°C by cast casting, the thick sheet is biaxially stretched into a film, the film is corona treated or flame treated into a mother roll, and the mother roll is slit after aging treatment to obtain the BOPP composite shrink film.

[0014] Furthermore, the composite antibacterial particles in the base layer have a particle size D50 of 5-10 μm.

[0015] Furthermore, the composite antibacterial particles in the base layer include stable composite antibacterial particles and uniform composite antibacterial particles.

[0016] Furthermore, the particle size of the stable composite antibacterial particles is 5-10 μm, and the particle size of the uniform composite antibacterial particles is 0.1-0.5 μm; wherein the mass ratio of the stable composite antibacterial particles to the uniform composite antibacterial particles is 1:(3-5).

[0017] Furthermore, the base layer masterbatch is prepared by first mixing polypropylene, stiffening masterbatch and antistatic masterbatch, then adding the heat-resistant metal ion particles in the stable composite antibacterial particles and the uniform composite antibacterial particles, stirring and melting, and then adding the nano titanium dioxide in the stable composite antibacterial particles and the uniform composite antibacterial particles.

[0018] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:

[0019] First, when the base layer also contains composite antibacterial particles, the antibacterial coverage of the entire membrane material is wider and the antibacterial effect is more significant, because the antibacterial particles not only exist in the outer layer, but also penetrate into the base layer, which greatly reduces the living space of bacteria or microorganisms on the entire membrane material; the outer layer is easily worn or scratched, and only the outer layer contains antibacterial particles. Once the outer layer is damaged, the antibacterial effect is reduced. When the base layer also contains antibacterial particles, even if the outer layer is damaged, the antibacterial particles in the base layer can continue to play a role, maintaining the antibacterial properties of the membrane material, and the composite antibacterial particles themselves have a certain mechanical support ability, which improves the toughness of the membrane. The composite antibacterial particles are evenly distributed in the two layers to form a more uniform antibacterial layer, avoiding the antibacterial effect being too strong or too weak locally, thereby improving the overall antibacterial efficiency;

[0020] Secondly, the larger particle size makes the dispersion of antibacterial particles in BOPP film more stable, reduces the aggregation and sedimentation of particles, and thus prolongs the antibacterial effect; antibacterial particles with increased particle size are easier to disperse evenly during the melt extrusion process, reducing fluctuations and instability during processing, and improving production efficiency and product quality; although the particle size of antibacterial particles has a relatively small effect on the mechanical properties of BOPP film, appropriately increasing the particle size enhances the rigidity and wear resistance of the film and improves its mechanical properties; antibacterial particles with larger particle size are easier to prepare and disperse, thereby reducing production costs. In addition, larger particle size may reduce the amount of antibacterial particles used, further reducing costs; antibacterial particles with increased particle size are more stable and less susceptible to environmental factors, thereby improving the performance of BOPP film in harsh environments;

[0021] Third, the mixed distribution of large and small particle sizes makes the membrane have better mechanical properties. Large particles provide strength, while small particles fill the pores, enhancing the density and toughness of the membrane. The filling of small particles reduces the porosity of the membrane and affects the permeability of the membrane. The addition of composite antibacterial particles can improve the antibacterial properties of the membrane. The mixing of large and small particle sizes makes the antibacterial particles more evenly distributed in the membrane, thereby improving the overall antibacterial effect. Small particles are filled between large particles to reduce porosity and improve the density of the membrane. Small particles have a larger specific surface area and can more effectively contact with bacteria and other microorganisms to play an antibacterial role. The mixed distribution of large and small particle sizes makes the membrane have better strength and toughness. The improvement of antibacterial properties reduces the pollution and damage of the membrane, thereby extending its service life.

[0022] Fourthly, nano-titanium dioxide has excellent antibacterial properties. By adding metal ion particles first, nano-titanium dioxide can be more evenly distributed in the film, thereby ensuring the uniformity of antibacterial properties. In addition, the high specific surface area of ​​nano-titanium dioxide enables it to contact bacteria more effectively and play an antibacterial role; metal ion particles form a skeleton structure in the base layer, which provides support for the filling of nano-titanium dioxide, making the nano-titanium dioxide dispersed and stable; nano-titanium dioxide is filled in the gaps between the glass beads to form a more compact filling structure, which improves the density and hardness of the film; DETAILED DESCRIPTION

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0024] Embodiment 1

[0025] The present application provides a method for preparing a BOPP composite shrink film, wherein the BOPP composite shrink film comprises an outer layer, a base layer, and a heat-sealing layer; the weight proportions of the functional layer, the base layer, and the heat-sealing anti-sticking layer are 3%-8%, 91%-98%, and 1%-5%, respectively; wherein the outer layer comprises: composite antibacterial particles: 1-2 parts, liquid coupling agent: 0.5-1 parts, antioxidant: 0.5-1 parts, dispersant: 0.1-0.3 parts, heat stabilizer: 0.1-0.3 parts, metallocene copolymer polypropylene: 70-80 parts, slip masterbatch: 5-8 parts, POE: 10-15 parts;

[0026] The base layer includes: polypropylene: 77-89 parts, rigidity masterbatch: 10-20 parts, antistatic masterbatch: 1-3 parts; the rigidity masterbatch includes a mixture of hydrogenated petroleum resin and homopolymer polypropylene (weight ratio is 1:1); composite antibacterial particles 2-5 parts;

[0027] Heat seal anti-sticking layer: polypropylene: 95-99 parts, titanium dioxide anti-sticking masterbatch: 1-5 parts;

[0028] The composite antibacterial particles include a mixture of nano titanium dioxide and heat-resistant metal ion particles, with a heat-resistant temperature of 500-600°C and a D50 particle size of 1-3 μm; the heat-resistant metal ion particles are submicron glass beads loaded with antibacterial ions, and the antibacterial ions include zinc ions, silver ions, and copper ions;

[0029] The preparation method of the composite antibacterial particles is as follows: heat-resistant metal ion particles made of 60 parts by weight of submicron glass beads, 15 parts by weight of silver ion salt, 13 parts by weight of zinc ion salt and 10 parts by weight of copper ion salt are mixed with nano titanium dioxide in a weight ratio of 1:1;

[0030] The preparation method of the outer layer masterbatch includes: pouring metallocene copolymer polypropylene, smooth masterbatch and POE into a high-speed mixer and mixing for 5-10 minutes; evenly spraying the liquid coupling agent into the particles; pouring the heat-resistant metal ion antibacterial agent, heat stabilizer, antioxidant, dispersant, mixing for 15-30 minutes to complete the mixing of the masterbatch materials; extruding through a twin-screw granulator, drawing, cooling and pelletizing with 0-7°C water, and drying to make a functional masterbatch.

[0031] The preparation method of the BOPP composite shrink film comprises: feeding the selected raw materials into a melt extruder according to the mass proportion, processing the raw materials into a melt in the melt extruder, passing the melt through a metering extruder, a filter, and a die head, and co-extruding a cast sheet at 200-250° C. into a thick sheet, biaxially stretching the thick sheet into a film, corona-treating or flame-treating the film into a mother roll, and slitting the mother roll after aging treatment to obtain the BOPP composite shrink film.

[0032] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0033] When the base layer also contains composite antibacterial particles, the antibacterial coverage of the entire membrane material is wider and the antibacterial effect is more significant, because the antibacterial particles not only exist in the outer layer, but also penetrate into the base layer, which greatly reduces the living space of bacteria or microorganisms on the entire membrane material; the outer layer is easily worn or scratched, and only the outer layer contains antibacterial particles. Once the outer layer is damaged, the antibacterial effect is reduced. When the base layer also contains antibacterial particles, even if the outer layer is damaged, the antibacterial particles in the base layer can continue to play a role, maintaining the antibacterial properties of the membrane material, and the composite antibacterial particles themselves have a certain mechanical support ability, which improves the toughness of the membrane. The composite antibacterial particles are evenly distributed in the two layers to form a more uniform antibacterial layer, avoiding the antibacterial effect being too strong or too weak locally, thereby improving the overall antibacterial efficiency;

[0034] The addition of composite antibacterial particles makes the surface of the film rougher, increasing the friction between the film and the packaged object, making the film fit the packaged object more closely during the shrinking process. In addition, the solid particles can also fix the film on the packaged object like an "anchor point" to prevent the film from slipping or falling off during the shrinking process;

[0035] The addition of composite antibacterial particles improves its heat shrinkage performance, forms a "heat bridge" in the film, promotes the conduction and distribution of heat in the film, and enables the film to shrink more evenly when heated. It also enhances the stability of the film and prevents the film from breaking due to stress concentration during the shrinkage process. The particles form a "buffer layer" in the film to absorb and disperse stress, thereby protecting the film from being damaged; the film can achieve a higher shrinkage rate under the same heating conditions, because the composite antibacterial particles change the thermal shrinkage behavior and mechanical properties of the film, so that the film can more effectively adapt to the shape and size of the packaged object during the shrinkage process; because the composite antibacterial particles form a "guide structure" in the film, guiding the film to shrink along a specific direction or path during the shrinkage process, thereby avoiding the phenomenon of uneven shrinkage or local excessive shrinkage;

[0036] Because the antibacterial particles are distributed in both layers, the membrane material has a more comprehensive protection capability against microorganisms such as bacteria and mold. Both the outer and inner layers can effectively inhibit the growth of microorganisms. The uniform distribution of antibacterial particles and their penetration into the base layer make the membrane material's antibacterial properties more durable, and it can still maintain a good antibacterial effect even after long-term use and multiple cleanings; it also makes the overall heat resistance or temperature sensitivity more uniform, making its quality more uniform and extending its service life.

[0037] The BOPP antibacterial touch shrink cigarette film of this embodiment was tested for cigarette film, wherein the outer layer was 5%, the base layer was 92%, and the heat-sealing anti-sticking layer was 3%. The samples are shown in Table 1:

[0038]

[0039] Table 1

[0040] Test items, test methods and test values ​​are shown in Table 2:

[0041] Test items Test Method index Sample 1 Sample 2 Sample 3 Sample 4 Heat seal strength (N / 15mm) YC / T266-2008 ≥2.4 3.4 3.6 3.5 3.8 Heat sealing temperature(℃) 110-140 130 130 130 130 Haze(%) GB / T2410 ≤2.0 1.8 1.8 1.8 1.9 Glossiness(%) GB / T8807 ≥85 97.8 98.0 97.6 98.3 <![CDATA[Water vapor transmission rate (g / m 2 ·24h·0.1mm)]]> GB / T1037 ≤2.0 1.86 1.88 1.86 1.92

[0042] Table 2

[0043] Embodiment 2

[0044] The above embodiment further improves the first embodiment by adding composite antibacterial particles into the base layer to increase the overall heat sealing ability and antibacterial effect of the film, in order to improve the stability of the shrink film.

[0045] The D50 particle size of the composite antibacterial particles in the base layer is 5-10 μm.

[0046] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0047] Compared with the composite antibacterial particles with a smaller particle size used in Example 1, the larger particle size makes the dispersion of the antibacterial particles in the BOPP film more stable, reduces the aggregation and sedimentation of the particles, and thus prolongs the antibacterial effect; the antibacterial particles with an increased particle size are more easily dispersed evenly during the melt extrusion process, reduce fluctuations and instability during the processing process, and improve production efficiency and product quality; although the particle size of the antibacterial particles has a relatively small effect on the mechanical properties of the BOPP film, appropriately increasing the particle size enhances the rigidity and wear resistance of the film and improves its mechanical properties; antibacterial particles with a larger particle size are easier to prepare and disperse, thereby reducing production costs. In addition, a larger particle size may reduce the amount of antibacterial particles used, further reducing costs; antibacterial particles with an increased particle size are more stable and less susceptible to environmental factors, thereby improving the performance of the BOPP film in harsh environments;

[0048] And because the particle size of the composite antibacterial particles in the base layer increases, gaps appear between the composite antibacterial particles and the base layer. Under heat sealing or other high temperature and harsh conditions, the outer layer masterbatch invades the gaps, making the overall film more bondable and more stable.

[0049] The samples were tested for cracking time in an environment of 50 pphm ozone concentration, 40°C, and 65% humidity according to the method of GB / T 7762-2003. The difference between the samples and Example 1 is that the particle size D50 of the composite antibacterial particles in the base layer is 10 μm. The results are shown in Table 3:

[0050] Sample 1 Sample 2 Sample 3 Sample 4 Cracking time (h) 216 246 224 262

[0051] Table 3

[0052] Embodiment 3

[0053] Embodiment 2 increases the particle size of the particles in the base layer to increase the stability of the film. In order to improve the uniformity of the particles in the film, further improvements are made on the basis of Embodiment 2.

[0054] The composite antibacterial particles in the base layer include stable composite antibacterial particles and uniform composite antibacterial particles, wherein the particle size of the stable composite antibacterial particles is 5-10 μm, and the particle size of the uniform composite antibacterial particles is 0.1-0.5 μm; wherein the mass ratio of the stable composite antibacterial particles to the uniform composite antibacterial particles is 1:(3-5).

[0055] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0056] The mixed distribution of large and small particle sizes makes the membrane have better mechanical properties. Large particles provide strength, while small particles fill the pores and enhance the density and toughness of the membrane. The filling of small particles reduces the porosity of the membrane and affects the permeability of the membrane. The addition of composite antibacterial particles can improve the antibacterial properties of the membrane. The mixing of large and small particle sizes makes the antibacterial particles more evenly distributed in the membrane, thereby improving the overall antibacterial effect. Small particles are filled between large particles to reduce porosity and improve the density of the membrane. Small particles have a larger specific surface area and can more effectively contact with bacteria and other microorganisms to play an antibacterial role. The mixed distribution of large and small particle sizes makes the membrane have better strength and toughness. The improvement of antibacterial properties reduces the pollution and damage of the membrane, thereby extending its service life.

[0057] By adjusting factors such as particle distribution and membrane thickness, the permeability of the membrane is controlled, and the small particles are further mixed with the outer membrane in the gaps to improve the integrity. The particles in the outer membrane are agglomerated between large particles so that more particles are gathered on the side close to the large particles, making it difficult for the particles in the outer membrane to fall off after friction and other external influences, and the antibacterial ability is not reduced over a long period of time.

[0058] The stability of each sample was tested according to the method of Example 2. The difference between the sample and Example 2 is that the composite antibacterial particles in the base layer include stable composite antibacterial particles and uniform composite antibacterial particles, wherein the particle size of the stable composite antibacterial particles is 10 μm, and the particle size of the uniform composite antibacterial particles is 0.1 μm; wherein the mass ratio of the stable composite antibacterial particles to the uniform composite antibacterial particles is 1:5. The results are shown in Table 4:

[0059] Sample 1 Sample 2 Sample 3 Sample 4 Cracking time (h) 235 251 234 271

[0060] Table 4

[0061] Embodiment 4

[0062] Example 3 controls the permeability of the membrane by combining particles of different sizes and improves the ability of the membrane to combine with the particles. In order to reduce the agglomeration phenomenon, the density and hardness of the membrane are further improved. This is an improvement based on Example 3.

[0063] When preparing the base layer masterbatch, polypropylene, rigidity-enhancing masterbatch and antistatic masterbatch are first mixed, and then the heat-resistant metal ion particles in the stable composite antibacterial particles and the uniform composite antibacterial particles are added, and after stirring and melting, the nano titanium dioxide in the stable composite antibacterial particles and the uniform composite antibacterial particles is added; that is, the heat-resistant metal ion particles in the composite antibacterial particles are added first, and then the nano titanium dioxide is added.

[0064] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0065] First, metal ion particles are added. Due to their relatively large particle size, a certain skeleton structure is formed in the base layer. Then, nano-titanium dioxide is added to fill the gaps between the glass beads to form a more compact filling structure, making the nano-titanium dioxide evenly dispersed and reducing its agglomeration. The addition of metal ion particles enhances the mechanical properties of the membrane, such as strength and toughness, while the filling of nano-titanium dioxide further improves the density and hardness of the membrane. The layered addition method improves the mechanical properties of the membrane more evenly.

[0066] Nano-titanium dioxide has excellent antibacterial properties. Metal ion particles are added first, so that nano-titanium dioxide can be more evenly distributed in the film, thereby ensuring the uniformity of antibacterial properties. In addition, the high specific surface area of ​​nano-titanium dioxide enables it to contact bacteria more effectively and play an antibacterial role; metal ion particles form a skeleton structure in the base layer, which provides support for the filling of nano-titanium dioxide, making the nano-titanium dioxide dispersed and stable; nano-titanium dioxide is filled in the gaps between the glass beads, forming a more compact filling structure, which improves the density and hardness of the film;

[0067] The layered addition method makes the nano-titanium dioxide evenly dispersed and reduces its agglomeration, thereby improving the uniformity and stability of the film. The layered addition of metal ion particles, submicron glass beads and nano-titanium dioxide improves the mechanical properties of the film more evenly and enhances the strength and toughness of the film.

[0068] The stability of each sample was tested according to the method of Example 3. The difference between the sample and Example 2 is that the heat-resistant metal ion particles are first added to the composite antibacterial particles in the base layer, and then nano-titanium dioxide is added. The results are shown in Table 5:

[0069] Sample 1 Sample 2 Sample 3 Sample 4 Cracking time (h) 252 268 253 278

[0070] Table 5

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a BOPP composite shrink film, characterized in that: The BOPP composite shrink film includes: an outer layer, a base layer, and a heat-sealing layer; the weight proportions of the functional layer, the base layer, and the heat-sealing anti-sticking layer are 3%-8%, 91%-98%, and 1%-5% respectively; wherein, the outer layer includes: composite antibacterial particles: 1-2 parts, liquid coupling agent: 0.5-1 parts, antioxidant: 0.5-1 parts, dispersant: 0.1-0.3 parts, heat stabilizer: 0.1-0.3 parts, metallocene copolymer polypropylene: 70-80 parts, slip masterbatch: 5-8 parts, POE: 10-15 parts; The base layer includes: polypropylene: 77-89 parts, rigidity masterbatch: 10-20 parts, antistatic masterbatch: 1-3 parts; the rigidity masterbatch includes a mixture of hydrogenated petroleum resin and homopolymer polypropylene; composite antibacterial particles 2-5 parts; Heat-seal anti-sticking layer: polypropylene: 95-99 parts, titanium dioxide anti-sticking masterbatch: 1-5 parts.

2. The method for preparing a BOPP composite shrink film according to claim 1, characterized in that: The composite antibacterial particles include a mixture of nano titanium dioxide and heat-resistant metal ion particles, with a heat-resistant temperature of 500-600°C and a D50 particle size of 0.1-10 μm.

3. The method for preparing a BOPP composite shrink film according to claim 2, characterized in that: The heat-resistant metal ion particles are submicron glass beads loaded with antibacterial ions, and the antibacterial ions include zinc ions, silver ions, and copper ions.

4. The method for preparing a BOPP composite shrink film according to claim 3, characterized in that: The preparation method of the composite antibacterial particles is as follows: heat-resistant metal ion particles composed of 60 parts by weight of submicron glass beads, 15 parts by weight of silver ion salt, 13 parts by weight of zinc ion salt and 10 parts by weight of copper ion salt are mixed with nano titanium dioxide in a weight ratio of 1:

1.

5. The method for preparing a BOPP composite shrink film according to claim 4, characterized in that: The D50 particle size of the composite antibacterial particles in the outer film is 1-3 μm.

6. The method for preparing a BOPP composite shrink film according to claim 1, characterized in that: The preparation method of the BOPP composite shrink film comprises: feeding the selected raw materials into a melt extruder according to the mass proportion, processing the raw materials into a melt in the melt extruder, passing the melt through a metering extruder, a filter, and a die head, and co-extruding a cast sheet at 200-250° C. into a thick sheet, biaxially stretching the thick sheet into a film, corona-treating or flame-treating the film into a mother roll, and slitting the mother roll after aging treatment to obtain the BOPP composite shrink film.

7. The method for preparing a BOPP composite shrink film according to claim 4, characterized in that: The D50 particle size of the composite antibacterial particles in the base layer is 5-10 μm.

8. The method for preparing a BOPP composite shrink film according to claim 4, characterized in that: The composite antibacterial particles in the base layer include stable composite antibacterial particles and uniform composite antibacterial particles.

9. The method for preparing a BOPP composite shrink film according to claim 8, characterized in that: The particle size of the stable composite antibacterial particles is 5-10 μm, and the particle size of the uniform composite antibacterial particles is 0.1-0.5 μm; wherein the mass ratio of the stable composite antibacterial particles to the uniform composite antibacterial particles is 1:(3-5).

10. The method for preparing a BOPP composite shrink film according to claim 9, characterized in that: The preparation of the base layer masterbatch is specifically as follows: first, polypropylene, stiffness-enhancing masterbatch and antistatic masterbatch are mixed, then the heat-resistant metal ion particles in the stable composite antibacterial particles and the uniform composite antibacterial particles are added, and after stirring and melting, the nano titanium dioxide in the stable composite antibacterial particles and the uniform composite antibacterial particles is added.

Citation Information

Patent Citations

  • A BOPP antibacterial touch shrink cigarette film and its preparation method and application

    CN116512717B

  • Preparation technology of antibacterial and mildew-proof masterbatch, antibacterial and mildew-proof type cross-linking hot shrink film and preparation technology of antibacterial and mildew-proof type cross-linking hot shrink film

    CN110387053A

  • Antibacterial PE shrink film and processing method thereof

    CN111269483A

  • BOPP (Biaxially-oriented Polypropylene) antibacterial touch shrinkage smoke film as well as preparation method and application thereof

    CN116512717A